2022
DOI: 10.1093/nar/gkac596
|View full text |Cite
|
Sign up to set email alerts
|

Double-stranded RNA drives SARS-CoV-2 nucleocapsid protein to undergo phase separation at specific temperatures

Abstract: Nucleocapsid protein (N-protein) is required for multiple steps in betacoronaviruses replication. SARS-CoV-2-N-protein condenses with specific viral RNAs at particular temperatures making it a powerful model for deciphering RNA sequence specificity in condensates. We identify two separate and distinct double-stranded, RNA motifs (dsRNA stickers) that promote N-protein condensation. These dsRNA stickers are separately recognized by N-protein's two RNA binding domains (RBDs). RBD1 prefers structured RNA with seq… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
48
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(52 citation statements)
references
References 82 publications
4
48
0
Order By: Relevance
“…IDRs in the full-length protein are also known to promote liquid-liquid phase separation (LLPS) in the presence of RNA indicating an intricate system of protein-RNA interactions at the basis of the function of the N-protein 1215 . Both CTD and NTD subdomains can also phase separate from a solution under a variety of external conditions 15,16 . Although the structural details of N-RNA recognition could be of crucial importance for the rational design of novel drugs, current techniques are limited by this Nucleocapsid condensation behaviour in the presence of RNA in solution, which precludes high-resolution structural determination.…”
Section: Introductionmentioning
confidence: 99%
“…IDRs in the full-length protein are also known to promote liquid-liquid phase separation (LLPS) in the presence of RNA indicating an intricate system of protein-RNA interactions at the basis of the function of the N-protein 1215 . Both CTD and NTD subdomains can also phase separate from a solution under a variety of external conditions 15,16 . Although the structural details of N-RNA recognition could be of crucial importance for the rational design of novel drugs, current techniques are limited by this Nucleocapsid condensation behaviour in the presence of RNA in solution, which precludes high-resolution structural determination.…”
Section: Introductionmentioning
confidence: 99%
“…First signs of LLPS (7 ± 3 droplets per mm 2 coverslip with a total area equal to 38 ± 10 µm 2 ) appeared at N concentration equal to 3 µM after overnight incubation ( Figure 2 a), and the apparent partitioning coefficient (PC = F droplet /F solution ) was equal to 9 ± 6. For subsequent experiments with RNA, we selected N concentration equal to 3 µM, because it has been used in previous studies of N-gRNA LLPS [ 7 ], is close to the previously reported saturation concentration detected in a cell-free system with non-viral RNA [ 6 ], and can be achieved in infected cells rapidly after virion unpackaging [ 6 , 18 ].…”
Section: Resultsmentioning
confidence: 99%
“…In particular, they are implicated in replication [ 3 ], immune evasion [ 4 ], and virion packaging [ 5 ]. Justifying the search for specific modulators of the LLPS-mediated steps of the SARS-CoV-2 cycle, the unique molecular grammar of N-gRNA condensates has recently been uncovered [ 6 , 7 ]. It comprises key elements of N and gRNA primary and secondary structures (“stickers”) that define transient heterotypic (N-RNA) or homotypic (N-N) interactions within droplets, as well as droplet plasticity-defining elements (“spacers”) in-between stickers.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations